Substituted dithiomalonamides as inhibitor for the corrosion of AISI 304SS in phosphoric acid-hydrochloric acid mixture - Kumar A.; Singh M.M. (My University, 2025)
The corrosion inhibitive efficiencies of substituted dithiomalonamides have been determined at different concentrations for 304 SS in H3PO4-HCI mixture at 25°C using potentiostatic technique. The percentage inhibition efficiencies have been found to increase with increasing concentrations of inhibitors. 1,5-Di-p-methylphenyl-2,4-Dithiomalonamide was found to be the most effective inhibitor followed by: 1,5-Di-p-methoxyphenyl-2,4-Dithiomalonamide, 1,5-Di-phenyl-2,4-Dithiomalonamide, 1,5-Di-p-cholorophenyl-2,4-Dithoimalonamide. Marked influence of the inhibitors is observed in decreasing the critical current density and enlarging the passive range. © 1993, MCB UP Limited